Lipocalin-2 abrogates epithelial cell cycle arrest by PPARγ inhibition. (November 2018) - Jung, Michaela; Brüne, Bernhard; Knethen, Andreas; Guiteras, Roser; Cruzado, Josep; Hotter, Georgina; Sola, Anna
Abstract Macrophage-epithelial cross-talk regulates cell cycle progression and represents an important factor in rescuing epithelial cells from cell cycle arrest in order to maintain a healthy epithelial phenotype. However, the underlying mechanisms are still not well defined. We provide evidence that macrophage-secreted lipocalin-2 (Lcn-2) plays a key role during this process. In a co-culture setup using cell cycle arrested NRK52e renal epithelial cells and primary bone marrow-derived macrophages, Lcn-2 restores proliferation through inhibition of peroxisome proliferator-activated receptor (PPAR)-γ. Lcn-2 overexpression in macrophages overcomes epithelial cell cycle arrest and enhances epithelial markers via megalin and the downstream activation of PI3K/Akt signalling pathway, whereas a knockdown of Lcn-2 in macrophages prevented this effect. Our results show that macrophage-secreting Lcn-2 is crucial in rescuing epithelial cells from cell cycle arrest and in promoting epithelial proliferation. Macrophage-epithelial crosstalk regulates cell cycle progression and is essential for the maintenance of a healthy epithelial phenotype. In the present work, the authors show that macrophage-secreted lipocalin-2 is crucial in rescuing epithelial cells from cell cycle arrest and in promoting epithelial proliferation through inhibition of peroxisome proliferator-activated receptor (PPAR)-γ. Lipocalin-2 maintains the epithelial cytoskeleton structure via megalin and downstream activation of thePI3K/AKT signaling pathway.